The Effect of Service Quality and Digital Promotional Strategies on Gen Z Customers’ Satisfaction with Mobile Banking (Case Study of BTN Syariah Kudus) - Putri Aria; Ahmad Fauzan Mubarok; Miswan Ansori (Universitas Wahid Hasyim Semarang, 2026)
This study aims to analyze the influence of mobile banking service quality and digital promotion strategies on user satisfaction with BTN Syariah Mobile among Gen Z customers at the BTN Syariah Kudus Sub-Branch Office (KCP). The research adopts a quantitative approach with an associative type of study. The population consists of Gen Z customers who are active users of BTN Syariah Mobile in Kudus, with a sample of 90 respondents selected using the purposive sampling method. Data analysis techniques include instrument testing, classical assumption testing, and multiple linear regression analysis conducted via SPSS. The partial results of the study indicate that service quality has a positive and significant effect on user satisfaction (t-count 2.258 > 1.987; Sig 0.026 < 0.05). Digital promotion strategy also has a positive and significant effect on user satisfaction (t-count 3.846 > 1.987; Sig 0.000 < 0.05). Simultaneously, both variables significantly influence user satisfaction with an F-value of 30.432 and a significance value of 0.000. The Adjusted R Square value of 0.398 indicates that service quality and digital promotion contribute 39.8% to the satisfaction of using BTN Syariah Mobile, while the remaining percentage is influenced by other factors outside this research model.